2004
DOI: 10.1086/382655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anatomic Changes in Young Children with Natural Rotavirus Infection: Is Intussusception Biologically Plausible?

Abstract: Rotavirus infection was associated with increased distal ileum wall thickness and lymphadenopathy during the illness period. These changes suggest a plausible mechanism by which rotavirus infection could cause intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 24 publications
(34 reference statements)
2
42
0
1
Order By: Relevance
“…Around the time of the licensure of the rhesus rotavirus vaccine in the late 1990s, many ecological studies compared the seasonal patterns of intussusception and hospitalizations for rotavirus infection, and found that they differed substantially; this finding suggests that rotavirus is not a major cause of intussusception [10,14,16,[31][32][33]. An assessment of patients with intussusception and healthy control subjects with use of ultrasound reported that rotavirus infection was associated with increased distal ileum wall thickness and lymphadenopathy during the illness period, suggesting a plausible mechanism by which rotavirus infection could cause intussusception [34]. However, several epidemiologic studies using the case-control approach that have examined association of intussusception with either all diarrheal diseases or laboratory-confirmed rotavirus disease have failed to show an association [19,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Around the time of the licensure of the rhesus rotavirus vaccine in the late 1990s, many ecological studies compared the seasonal patterns of intussusception and hospitalizations for rotavirus infection, and found that they differed substantially; this finding suggests that rotavirus is not a major cause of intussusception [10,14,16,[31][32][33]. An assessment of patients with intussusception and healthy control subjects with use of ultrasound reported that rotavirus infection was associated with increased distal ileum wall thickness and lymphadenopathy during the illness period, suggesting a plausible mechanism by which rotavirus infection could cause intussusception [34]. However, several epidemiologic studies using the case-control approach that have examined association of intussusception with either all diarrheal diseases or laboratory-confirmed rotavirus disease have failed to show an association [19,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, G3 serotype was not a major VP7 serotype among strains circulating in Tunisia between 1995 and 1999 [44]. A recent intestinal ultrasound study showed that wild-type rotavirus induced a significantly greater number of lymph node aggregates and significantly greater thickening of the distal ileum than observed in control infants evaluated by use of coded examinations [45]. Moreover, Warfield et al [46] showed in a mouse model that rotavirus infection combined with lipopolysaccharide treatment increased the rates of intussusception compared to lipopolysaccharide treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is difficult to say whether intussusception was a problem unique to RotaShield or whether it will affect other live rotavirus vaccines. One recent study of 13 pairs of infants hospitalized with rotavirus diarrhea documented a spontaneously reversed intussusception event, as well as significant anatomic small-bowel changes and lymph-node aggregates, suggesting that natural rotavirus infections may be a prelude to intussusception [17]. By extension, then, any live rotavirus vaccine candidate may carry with it a risk of intussusception.…”
Section: Discussionmentioning
confidence: 99%